Powtoon as Learning Media to Improve Listening Skills in Children Aged 5-6 Years - Azizah, Anggita Nur; Sholeha, Vera; Pudyaningtyas, Adriani Rahma; Chitkrajang, Sittipat (Kumara Cendekia, 2026)
Listening skills is the ability to understand verbal and nonverbal information. These skills form the foundation for children’s language and communication development, but are often overlooked in learning, leaving children less active in processing information. The Powtoon application serves as a solution by presenting engaging and interactive learning experiences. This study aims to improve the listening skills of 5- to 6-year-old children at a kindergarten located in Colomadu, Karanganyar, by utilizing the Powtoon application as a learning medium. Classroom action research was conducted through collaboration between the researcher and the teacher up to cycle II, with each cycle consisting of three meetings. The stages of planning, implementation, observation, and reflection followed the Kemmis and McTaggart model. Data collection included observation, interviews, oral tests, and documentation, with both quantitative and qualitative analyses applied. Source and technique triangulations were carried out to ensure data validity. The research was guided by specific indicators, namely the ability in maintaining attention for 10–15 minutes, answering questions based on the information heard, and retelling information in the correct sequence. The research findings indicate that children’s listening skills improved after utilizing the Powtoon application as a learning medium. Classical improvement progressed from 21.43% in the pre-intervention stage to 57.12% in cycle I, and reached 85.71% in cycle II. These findings demonstrate that the Powtoon application plays an important role in improving the listening skills of 5- to 6-year-old children at a kindergarten located in Colomadu, Karanganyar.